Managed artificial recharge through drywells - Olivares M., Yerko; Herrera R., Paulo (Tecnología y ciencias del agua, 2024)
Managed aquifer recharge (MAR) is a water management strategy that uses aquifers for the seasonal or inter-annual storage of exceeding surface water. Systems that implement artificial recharge use infiltration ponds or shallow or deep infiltration wells. While articifial recharge through infiltration ponds requires large areas and infiltration through deep wells demands high investment, infiltration through drywells, which inject water to the vadose zone, is often a preferred option because of its low cost and relatively easy implementation. We present results of detailed numerical simulations to assess the operation of a single drywell to implement an artificial recharge system. We demonstrate that depending upon the distribution and property of the geological materials that compose the subsurface, the operation of the well can produce quite different results in terms of effective recharge. We expect that these findings will help design real MAR systems and provide supporting information for decision-makers in charge of approving and financing such water management systems.